ap3813
Answered

At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

solve this using substitution:
5x-y=-3
6x+y=3


Sagot :

Answer:

x=0.y=3

Step-by-step explanation:

5x-y=-3

y=5x+3

sub y=5x+3 into 6x+y=3,

6x+5x+3=3

11x=0

x=0

6(0)+y=3

y=3

k11037
the answer is x-0 y-3